Islamic Education in Secondary Schools in Germany: Challenges and Hopes - Usdarisman Usdarisman; Meirison Meirison; Qasem Muhammadi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
In Germany, there is no recognition of Muslims as an official religious sect, in addition to the fact that educational issues are within the jurisdiction of the state. Diversity in education is a loophole for Muslims to organize education in the community, given this diversity. In terms of teaching religious subjects, German states stand independently. This article is based on a literature study that collects documents from books and journals through a qualitative approach to the phenomenon of education obtained in various literatures and interpreted descriptively. The way the Muslim generation in Europe learns their religion is one of the most critical problems faced by Muslims there, both at the individual and community levels. Every religious sect has the constitutional right to teach religion to its adherents. Discussions on this topic began in Germany 40 years ago with the question of the conditions under which Islamic religious education can be provided in public schools, and the discussion continues to this day. Since the state has autonomy in education, we can find different models of religious lessons in each state and other obstacles, such as teaching staff and learning materials; therefore, the right legal formula must be sought to teach religion to the Muslim generation correctly.